2013
DOI: 10.1007/s10661-013-3382-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air-drying and oven-drying treatment on Cr(VI) content and Cr bond forms in soil

Abstract: Air-drying and oven-drying are pretreatment processes often used before testing and analyzing various soil characteristics in the laboratory. This study selected three kinds of soil, including red soil, entisol, and alluvial soil, and examined the variation of the Cr(VI) content and Cr bond forms in these soils during air-drying and oven-drying. The results show that when the soil is air-dried in natural environment, the Cr(VI) content decreases with air-drying time. On day 10 of air-drying, the Cr(VI) content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition, the stable occurrence fractions of Cr in soil greatly reduced the environmental toxicity (Barajas- Aceves et al, 2007;Pérez et al, 2008). These results indicated that the environmental toxicity of Cr was restricted by soil water content (Cheng et al, 2014). Shaheen et al (2014) concluded that the dynamic migration of Cr was related to the duration of soil exposure to floods, because drivers of Cr element mobility required a certain amount of time to provoke reactions under shifting conditions.…”
Section: Effects Of Dry and Wet Conditions On The Stabilization Of Cr...mentioning
confidence: 98%
“…In addition, the stable occurrence fractions of Cr in soil greatly reduced the environmental toxicity (Barajas- Aceves et al, 2007;Pérez et al, 2008). These results indicated that the environmental toxicity of Cr was restricted by soil water content (Cheng et al, 2014). Shaheen et al (2014) concluded that the dynamic migration of Cr was related to the duration of soil exposure to floods, because drivers of Cr element mobility required a certain amount of time to provoke reactions under shifting conditions.…”
Section: Effects Of Dry and Wet Conditions On The Stabilization Of Cr...mentioning
confidence: 98%